NON-DESTRUCTIVE LEAK DETECTION IN GALVANIZED IRON PIPE USING NONLINEAR ACOUSTIC MODULATION METHOD - Gigih Priyandoko (SINERGI, 2018)
Non-destructive testing is a wide group of analysis techniques used in science and industry to evaluate the properties of a structure without causing damage to it. The main objective of this project is to carry out experiment to detect leakage in pipeline using nonlinear acoustic modulation method. The nonlinear acoustic modulation approach with low frequency excitation and high frequency acoustic wave is used to reveal modulations in the presence of leak. The pipe used in this experiment was galvanized iron pipe. The experiment is started with the experiment of undamaged specimen and followed by the experiment of damaged specimen with manually applied leak. The results obtained are being observed and the difference between the specimen without leak and with leak can be distinguished. The distance of the leak and the distance of the outlet detected is nearly accurate to the exact location which is leak at 4.0 m and outlet at 6.0 m. Therefore, the results demonstrate that leakage can be detected using nonlinear acoustic modulation, and proved the objective of distinguish the difference between the results of specimen without leak and with leak has succeeded. The damage detection process can be eased with the knowledge on the signal features.